Cystatin C Levels in Middle-Aged Patients with Obstructive Sleep Apnea Syndrome. (24th October 2016) - Archontogeorgis, Kostas; Nena, Evangelia; Tsigalou, Christina; Voulgaris, Athanasios; Xanthoudaki, Maria; Froudarakis, Marios; Steiropoulos, Paschalis
Abstract : Background . Obstructive sleep apnea syndrome (OSAS) is associated with systemic inflammation and increased risk of cardiovascular and chronic kidney disease. Cystatin C (Cyst C) is a novel biomarker of both latent renal damage and cardiovascular disease. Aim of the study was to measure serum levels of Cyst C, as well as IL-8 and CRP, in otherwise healthy OSAS patients. Methods . 84 individuals examined with polysomnography for OSAS symptoms without known comorbidities were prospectively recruited. Results . According to apnea hypopnea index (AHI) subjects were divided in two groups: OSAS group (AHI > 5/hour, n = 64 ) and controls (AHI < 5/hour, n = 20 ), which were age- and BMI-matched. Cyst C levels were higher in OSAS patients versus controls (1176.13 ± 351.33 versus938.60 ± 245.83 ng/mL, resp.;p = 0.017 ) while serum IL-8 and CRP levels did not differ significantly. Positive correlation was found between Cyst C levels and respiratory disturbance index (RDI) (r = 0.240, p = 0.039 ) and percentage of time with oxygen saturation <90% (r = 0.290, p = 0.02 ) and negative correlation was found between Cyst C levels and average oxygen saturation during sleep (r = - 0.291, p = 0.012 ). After adjustment for age and BMI, RDI was the only independent predictor of Cyst C levels ( β = 0.256, p = 0.039 ). Conclusion . Cyst C serum levels are increased in OSAS patients without comorbidities, suggesting an increased renal and cardiovascular disease risk.